FUNCTIONAL-SEMITIC AND LINGUCULTURAL STUDY OF THE NAMES OF WORKS OF ART IN THE UZBEK LANGUAGE - Akhmedov Umid (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In this article, the functional-sematic and lingucultural examination of the names of works in Uzbek language is explained. In this, with the help of additional science, anthroponyms and adjectives represent anthroponyms and adjectives in the language of the Uzbek language. Functional-semitic and linguistic-cultural research production of the names of works of art in Korazbek according to the semantic requirements of naming disease in linguistics is not only the content, but also the correct structure and interpretation show a secret is showing.